Live Food for Marine Fish Larvae - Kraul, Syd (Avances en Nutrición Acuicola, 2019)
The choice of a particular fish species for aquaculture starts a cascade of subsequent choices of live feeds for a fish hatchery. Once a fish species is chosen, the first larval feed (zooplankton such as copepods, rotifers or Artemia) may be chosen, and each of these zooplankters has different algae requirements for optimum performance. The first feed is usually determined by larval mouth size. For this discussion, the choices are large, medium and small mouth fish larvae. The fish chosen as examples here are species raised by the author, but many other species fall into similar categories of size and nutritional needs.